2016
DOI: 10.1002/acp.3235
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identity Predicts Autobiographical Memory Phenomenology

Abstract: Gender differences emerge regularly in autobiographical memory research. We suggest that gender differences in phenomenological self-report measures of autobiographical memory are rooted in gender identity rather than categorical gender. Reminiscing about the past is perceived as a female-typical activity, and therefore, gender-typical individuals will conform to these stereotypes. In this study, 196 participants, age 18-40, each rated the phenomenology of four event memories. Ratings of feminine gender identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Although there are no studies devoted to the autobiographical memory of transsexual individuals, it seems quite evident that congruency of the self to a gender stereotype, not gender itself, predicts those autobiographical memory characteristics that are in line with common beliefs about gender differences in memory (Grysman & Fivush, 2016). The authors indicated that the higher participants scored on the femininity scale, the more vivid, emotional, and easily shared with others their memories were, according to self-reports.…”
mentioning
confidence: 59%
“…Although there are no studies devoted to the autobiographical memory of transsexual individuals, it seems quite evident that congruency of the self to a gender stereotype, not gender itself, predicts those autobiographical memory characteristics that are in line with common beliefs about gender differences in memory (Grysman & Fivush, 2016). The authors indicated that the higher participants scored on the femininity scale, the more vivid, emotional, and easily shared with others their memories were, according to self-reports.…”
mentioning
confidence: 59%
“…With regard to the characteristics of the sample, we assume that the limited amount of gender difference can be attributed to it, and especially, the age of the participants and their high level of education. In this vein, Grysman, Fivush, and Merrill (Grysman & Fivush, 2016; Grysman, Merrill, & Fivush, 2016) have argued that rather than categorical gender, it is gender identity, to what extent do people (and, especially, women) identify with stereotypical gender norms, that predicts both the content and the phenomenological characteristics. This is in our view a very promising avenue for future research that may help us understand the complex relation between gender and AM.…”
Section: Discussionmentioning
confidence: 99%
“…Memories from a female narrative that are autobiographical in nature versus those by males have been examined in research to uncover gender differences. It appears that gender identity plays a larger part in recall than gender itself when studying these autobiographical narratives (Grysman & Fivush, 2016). More often researchers look at stereotypical gender identity as a means of comparison for predicted memory.…”
Section: Figure 1-3 Thoughts Of First Grade + My Beaded Medicine Bagmentioning
confidence: 99%
“…I reject being the voice in a category or a representative sample. Memories serve as reliable markers for a sense of self throughout our lifetimes (Grysman & Fivush, 2016).…”
Section: Indigenous Aspects Of Memorymentioning
confidence: 99%
See 1 more Smart Citation